Spatial Analysis and Development Dynamics of Kampung Kamal Muara via Coastal Mapping - Denny Husin (Advances in Civil Engineering and Sustainable Architecture, 2025)
This research aims to conduct a spatial mapping analysis for Kamal Muara Fisherman Kampung to understand the development dynamic of its housing fabric. It focuses on identifying and exploring the potential for spatial hybridity, a key factor in the transformation of the kampung’s physical layout. The study identifies a critical issue in the current spatial aggregation, which lacks optimal development and coherence, thereby emphasizing its character for strategic planning and design intervention. A qualitative interpretive methodology is employed, utilizing a typo-morphological approach. The primary research instrument involves digital mapping techniques. The mapping process consists of three main stages: (1) map extraction, (2) morphological analysis, and (3) typological synthesis. The expected outcome of this research is the formulation of a spatial algorithm for model development, with a particular emphasis on generating a prototype for residential units that could serve as the structural core of the kampung’s spatial network.